Enhancing Early Literacy and Numeracy Skills through Diverse Media - Multahada, Asyruni (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
Early childhood literacy and numeracy development are essential for cognitive and language growth. Introducing these skills at a young age is crucial, and media variation can enhance interest and motivation. This qualitative study, using a phenomenological approach, explored the use of media in early childhood literacy and numeracy education. Data was collected through interviews, observations, and documentation. Results indicate that media used includes humans (teachers), educational game tools, and varied learning programs. Variation techniques encompass combining media, varying methods within a medium, daily media changes, periodic media variety, and classroom-external media use.